An experimental investigation of federal messaging on public support for enforcement- and treatment-based approaches for opioid overdose prevention in South Carolina - Lídia Gual-Gonzalez; Hunter M. Boehme; Peter Leasure; Pieter A. Baker; Melissa S. Nolan (Health & Justice)
Abstract Background As the opioid overdose crisis continues to produce excessive morbidity and mortality in the United States, government agencies have applied various approaches to prevent overdoses, including law-enforcement efforts (e.g., arresting people who use drugs, interrupting drug traffickers, etc.) and treatment-based approaches (e.g., naloxone, medications for opioid use disorder, etc.). Public perception and support of these approaches are relevant for informing policy, allocating resources, and effectively implementing community interventions to prevent drug-related harms. Methods Using an embedded informational survey design, we experimentally assessed whether public support for strategies to prevent overdose in South Carolina is influenced by language from federal agencies describing treatment- or enforcement-based approaches. Respondents were randomly assigned to one of three groups: (1) enforcement -based approach, (2) treatment-based approach, or (3) the control condition. Those assigned to experimental groups were presented with statistics on drug overdose deaths, followed by an informational prompt with language about overdose prevention approaches from either DEA (enforcement) or NIH (treatment), while the control group received no informational prompt. Results Findings from a sample of 4,675 respondents indicated that those assigned the DEA prompt were significantly more likely to support enforcement-based approaches in arresting drug traffickers and people who use drugs (AME = 0.060, p < 0.001). On the other hand, those assigned to the NIH prompt were significantly more likely to agree that both law enforcement (AME = 0.065, p < 0.0001) and clinicians (AME = 0.044, p < 0.05) are capable of preventing drug overdose deaths. Conclusions These findings shed light on public perceptions of approaches to addressing the opioid epidemic and limited modifiability when presented with language from federal agencies. This may inform future research, practice, and/or policy aiming to maintain public safety while also providing treatment options to people who use drugs in order to reduce overdose deaths.